Japanese apologies for World War II : a rhetorical study - Yamazaki, Jane W. (Routledge contemporary Japan series, 2006)
Post-war Japan offers a compelling case study of national apologies for past wrongdoings. Actions of the Japanese Army and government during the Second World War caused enormous suffering and distress throughout Asia, leaving a legacy of resentment and distrust. Beginning in the mid-1980s, apology for wartime actions became a recurring issue for Japan. Repeated calls for apology from various quarters as well as repeated apologies by Japanese officials provide a rich source for the study of national apology and how public apology discourse develops over time. Unlike most rhetorical st.